Negative electrode material, its manufacturing method, and lithium ion battery
By using a combination of carbon material and silicon-based material in the negative electrode material of lithium-ion batteries, the porosity and structure of the material are controlled to form a surface carbon layer, which solves the problem of side reaction when the electrolyte comes into contact with the silicon-based material, and improves the cycle stability and electrochemical performance of the battery.
Patent Information
- Application Number
- JP2022527186
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-22
- Filing Date
- 2022-04-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-04-29
AI Technical Summary
In existing lithium-ion batteries, silicon-based negative electrode materials are prone to side reactions when they come into contact with the electrolyte, resulting in damage to the structure of the negative electrode materials, deterioration of electrochemical performance, poor cycle stability, and difficult to apply in practice.
Using a negative electrode material composed of carbon material and silicon-based material, by controlling the porosity and particle structure of the material, ensure that the porosity does not exceed 2.5%, and a carbon layer is formed on the surface to avoid electrolyte penetration and side reactions.
The side reaction between the electrolyte and the silicon-based material is effectively avoided, the cycle stability and electrochemical performance of the negative electrode material are improved, and the manufacturing cost is reduced.
Smart Images

Figure 0007664921000002 
Figure 0007664921000003 
Figure 0007664921000004
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of anode materials, in particular to anode materials and their manufacturing methods, and lithium ion batteries. [Background technology]
[0002] Conventional lithium-ion batteries have the advantages of high energy density, high output, long cycle life, and less environmental pollution, and are therefore widely used in electric vehicles and consumer electronics (CE). In order to increase the energy density of batteries, research and development of silicon-based anode materials is becoming mature. However, when the anode material comes into contact with the electrolyte, side reactions are likely to occur, which can destroy or disintegrate the structure of the anode material, leading to deterioration of electrochemical performance, capacity attenuation, and reduced cycle stability, making it difficult to put the battery into practical use.
[0003] Therefore, it is an urgent task to avoid side reactions caused by contact between the electrolyte and silicon-based materials and to improve the cycle stability of the materials. Summary of the Invention [Problem to be solved by the invention]
[0004] In view of the above problems, the present invention provides a negative electrode material and a manufacturing method thereof, which can effectively avoid side reactions caused by contact between an electrolyte and a silicon-based material and improve battery cycle characteristics, and a lithium-ion battery, and the manufacturing method can reduce manufacturing costs. [Means for solving the problem]
[0005] In a first aspect, a negative electrode material having an aggregate including a carbon material and a silicon-based material, the porosity W of the negative electrode material is 2.5% or less, and a quantity ratio P of particles having a pore size of more than 50 nm to the negative electrode material is 1% or less; The porosity is determined by measuring a pore volume ΔV of the negative electrode material by a pore distribution analysis method, measuring a true density P of the negative electrode material, and then calculating a porosity W of the negative electrode material by the following formula: W = ΔV / (ΔV+1 / P)
[0006] The negative electrode material according to the present invention has an aggregate containing an active material and a carbon material. The negative electrode material has a porosity W of 2.5% or less. When the porosity W is within this range, the electrolyte can be effectively prevented from penetrating directly into the inside of the negative electrode material particles through the porous structure, and side reactions caused by contact between the electrolyte and the silicon-based material can be effectively avoided. Furthermore, by controlling the quantitative ratio of the particles with a pore size of more than 50 nm in the negative electrode material to the negative electrode material, the side reactions between the electrolyte and the silicon-based material can be further avoided, and the electrolyte is also less likely to penetrate into the aggregate. The aggregate structure contributes to protecting the silicon-based material particles inside, and can effectively suppress the volume expansion of the negative electrode material, reduce the expansion rate, and improve the cycle characteristics of the battery.
[0007] In one embodiment, the negative electrode material further comprises a carbon layer present on at least a portion of the surface of the aggregates. In one embodiment, the aggregate includes a carbon material having a porous structure and a silicon-based material filled within the porous structure of the carbon material. In one embodiment, the aggregate includes a silicon-based material having a porous structure and a carbon material filled within the porous structure of the silicon-based material. In one embodiment, the silicon-based material has a median diameter of 1 nm to 500 nm. In one embodiment, the silicon-based material is 10% by mass to 70% by mass with respect to the negative electrode material. In one embodiment, the carbon material is present in an amount of 10% by mass to 50% by mass with respect to the negative electrode material. In one embodiment, the carbon material comprises at least one selected from the group consisting of artificial graphite, natural graphite, soft carbon, hard carbon, amorphous carbon, activated carbon, mesocarbon microbeads, carbon nanotubes, carbon nanofibers, porous carbon, and graphene. In one embodiment, the carbon material has a median diameter of 1 μm to 50 μm. In one embodiment, the silicon-based material includes at least one selected from the group consisting of elemental silicon, silicon oxide materials, and silicon alloys. In one embodiment, the silicon-based material has a porous structure. In one embodiment, the negative electrode material has a particle crushing strength of 400 MPa or more. In one embodiment, the aggregates further comprise a metal oxide. In one embodiment, the metal oxide is distributed between the carbon material and the silicon based material. In one embodiment, the metal oxide is distributed within the porous structure of the carbon material. In one embodiment, the metal oxide is distributed within the porous structure of the silicon-based material. In one embodiment, the metal oxide has the general formula: x O y (wherein 0.2≦y / x≦3; M includes at least one selected from the group consisting of Sn, Ge, Fe, Cu, Ti, Na, Mg, Al, Ca, and Zn). In one embodiment, the metal oxide is in the form of a sheet and / or a length. In one embodiment, the metal oxide has an aspect ratio greater than two. In one embodiment, the carbon layer comprises amorphous carbon. In one embodiment, the carbon layer has a thickness of 1 nm to 3000 nm. In one embodiment, the negative electrode material has a median diameter of 0.5 μm to 30 μm. In one embodiment, the negative electrode material has a specific surface area of 10 m 2 / g or less.
[0008] In a second aspect, there is provided a method for producing a negative electrode material, comprising the steps of: A step of classifying and mixing the carbon material, the silicon-based material, and the solvent to obtain a first precursor; mixing the first precursor, a first carbon source and an antifoaming agent and subjecting the mixture to a densification treatment to obtain a second precursor; and carbonizing the second precursor to obtain an aggregate. The classifying and mixing step provides a method including a vacuum impregnation process.
[0009] In the above technical proposal, the carbon material, the silicon-based material and the solvent are classified and mixed, and then vacuum impregnation is performed to obtain the first precursor, and the first precursor, the first carbon source and the antifoaming agent are mixed and carbonized to obtain an aggregate. In this process, the classified mixing improves the mixing uniformity of the different materials, reduces the voids caused by the deposition of the different materials, improves the deposition density, and reduces the holes caused by the deposition as much as possible. The vacuum impregnation process utilizes the action of the vacuum to further remove the gas adsorbed on the surface of the product, and further reduces the porosity. The addition of the antifoaming agent can reduce or remove the bubbles formed by the volatile matter during the carbonization process, which further contributes to the sufficient release of the volatile matter. The first carbon source generally produces a large amount of volatile matter during carbonization, and if these volatile matter are not released quickly, they are likely to remain inside after curing and form voids. The uniformly dispersed defoaming agent can penetrate into the foamed elastic film, and distributes throughout the film to reduce the surface tension of the foamed elastic film, thereby preventing cracks and allowing volatile matter to escape more smoothly. The densification treatment can further reduce some of the pores, making the material denser, reducing the porosity of the final negative electrode material, and reducing the proportion of macropores, making it difficult for the electrolyte to penetrate into the aggregates, which contributes to protecting the silicon-based material particles inside and reducing the probability of the electrolyte coming into contact with the silicon-based material, improving the structural stability of the negative electrode material, and improving the cycle characteristics of the battery.
[0010] In one embodiment, the silicon-based material has a median diameter of 1 nm to 500 nm. In one embodiment, the carbon material includes at least one selected from the group consisting of artificial graphite, natural graphite, soft carbon, hard carbon, amorphous carbon, activated carbon, mesocarbon microbeads, carbon nanotubes, carbon nanofibers, porous carbon, and graphene. In one embodiment, the mass ratio of the silicon-based material to the carbon material is (10-70):(10-50). In one embodiment, the silicon-based material has a porous structure. In one embodiment, the silicon-based material includes at least one selected from the group consisting of elemental silicon, silicon oxide materials, and silicon alloys. In one embodiment, the step of obtaining a first precursor includes thoroughly mixing a carbon material, a silicon-based material in a solvent, and then removing the solvent to obtain a first precursor. In one embodiment, the solvent comprises an organic solvent. In one embodiment, the alcohol comprises at least one selected from the group consisting of methanol, ethanol, ethylene glycol, propanol, isopropanol, glycerin, n-butanol, isobutanol, and pentanol. In one embodiment, a metal oxide is further added in the step of classifying and mixing the carbon material, the silicon-based material, and the solvent. In one embodiment, the metal oxide has the general formula: x O y (wherein 0.2≦y / x≦3; M includes at least one selected from the group consisting of Sn, Ge, Fe, Cu, Ti, Na, Mg, Al, Ca, and Zn). In one embodiment, the metal oxide is in the form of a sheet and / or a length. In one embodiment, the metal oxide has an aspect ratio greater than two. In one embodiment, the mass ratio of the metal oxide to the silicon-based material is (1-20:100). In one embodiment, the classification and mixing treatment method includes at least one selected from the group consisting of mechanical stirring, ultrasonic dispersion, and abrasive dispersion.
[0011] In one embodiment, the step of obtaining the first precursor includes classifying and mixing a carbon material, a silicon-based material, and a solvent, and then drying the mixture to obtain the first precursor. In one embodiment, the drying temperature is 40° C. to 600° C., and the drying time is 1 hour to 15 hours. In one embodiment, the mass ratio of the first precursor to the first carbon source is (10-80):100. In one embodiment, the first carbon source comprises at least one selected from the group consisting of sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, and asphalt. In one embodiment, the mass ratio of the first precursor to the antifoaming agent is (10-80):(0.4-14). In one embodiment, the antifoaming agent includes at least one selected from the group consisting of cetylbenzenesulfonic acid, polyether-modified silicone oil, monoamides, bisamides, trialkylmelamines, cyanuric acid chloride melamine, aliphatic amines, lauric acid, palmitic acid, fatty acid glycerides, polydimethylsiloxanes, polyacrylic acid, ethylene oxide, and propylene oxide. In one embodiment, the densification treatment includes at least one selected from the group consisting of a fusion treatment, a kneading extrusion treatment, an embossing treatment, and a dipping treatment.
[0012] In one embodiment, the fusion process is mechanofusion. In one embodiment, the rotation speed of the fusion device used for the mechanofusion is 10 r / min to 100 r / min. In one embodiment, said mechanofusion is at least 0.5 hours in duration. In one embodiment, the carbonization temperature is 600° C. to 1200° C., and the carbonization time is 1 hour to 10 hours. In one embodiment, the temperature increase rate in the carbonization treatment is 1° C. / min to 30° C. / min. In one embodiment, a protective gas containing at least one selected from the group consisting of nitrogen, helium, neon, argon and krypton is passed through during the carbonization process. In one embodiment, the method further includes subjecting the carbon material to an oxidation activation treatment before mixing the carbon material and the silicon-based material in a solvent and classifying and mixing. In one embodiment, the conditions of the oxidative activation treatment include placing the carbon material in a mixed gas containing at least one gas selected from the group consisting of air, carbon dioxide gas, and water vapor, and performing the oxidative activation treatment. In one embodiment, the temperature of the oxidation activation treatment is 400°C to 1200°C.
[0013] In one embodiment, the time for the oxidative activation treatment is 1 hour to 13 hours. In one embodiment, the method further comprises carbon coating the aggregates. In one embodiment, the method further comprises the step of carbon-coating the aggregates, the carbon-coating step comprising mixing the aggregates with a second carbon source and carbon-coating the aggregates. In one embodiment, the method further includes a step of carbon-coating the aggregate, the carbon-coating step including a step of mixing the aggregate with a second carbon source and carbon-coating the aggregate, the second carbon source including at least one selected from the group consisting of sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, and asphalt. In one embodiment, the method further includes a step of carbon-coating the aggregate, and the carbon-coating step includes mixing the aggregate with a second carbon source and carbon-coating the aggregate, and a mass ratio of the aggregate to the second carbon source is (20-100):(10-80). In one embodiment, the method further includes a step of carbon-coating the aggregate, the carbon-coating step including mixing the aggregate with a second carbon source and carbon-coating the aggregate, the temperature of the carbon-coating step being 600°C to 1200°C, and the time of the carbon-coating step being 1 h to 10 h.
[0014] In a third aspect, there is provided a lithium ion battery comprising the anode material according to the first aspect, or the anode material produced by the method according to the second aspect. Effect of the Invention
[0015] The technical solution of the present invention can achieve at least the following beneficial effects: The negative electrode material according to the present invention has an aggregate containing an active material and a carbon material. The porosity W of the negative electrode material is 2.5% or less, and within this range, it is possible to effectively prevent the electrolyte from directly penetrating into the inside of the negative electrode material particles through the porous structure, and effectively avoid side reactions caused by the contact between the electrolyte and the silicon-based material. Furthermore, by controlling the quantitative ratio of the particles with a pore size of more than 50 nm in the negative electrode material to the negative electrode material, the side reactions between the electrolyte and the silicon-based material are further avoided, and the electrolyte is also difficult to penetrate into the aggregate. The aggregate structure contributes to protecting the silicon-based material particles inside, effectively suppressing the volume expansion of the negative electrode material, reducing the expansion rate, and preventing the collapse of the internal structure of the aggregate, thereby improving the cycle characteristics of the battery.
[0016] Next, the method for producing the negative electrode material according to the present invention classifies and mixes the carbon material, the silicon-based material and the solvent, performs a vacuum impregnation process, obtains a first precursor, and mixes the first precursor, the first carbon source and the antifoaming agent to perform a carbonization process to obtain an aggregate. In this process, the classifying and mixing improves the mixing uniformity of the different materials, reduces the voids caused by the deposition of the different materials, improves the deposition density, and reduces the holes caused by the deposition as much as possible. The vacuum impregnation process utilizes the action of the vacuum to further remove the gas adsorbed on the surface of the product, and further reduces the porosity. The addition of the antifoaming agent reduces or removes the bubbles formed by the volatile matter during the carbonization process, further contributing to the release of the volatile matter. The first carbon source generally generates a large amount of volatile matter during carbonization, and if these volatile matter are not released quickly, they tend to remain inside after curing and form voids. The uniformly dispersed defoaming agent can penetrate into the foamed elastic film, and distributes throughout the film to reduce the surface tension, thereby preventing the foamed elastic film from cracking, and contributing to the smoother escape of volatile matter, thereby reducing some of the pores, making the material denser, reducing the porosity of the final negative electrode material, reducing the proportion of macropores, making it difficult for the electrolyte to penetrate into the aggregates, contributing to the protection of the silicon-based material particles inside, reducing the probability of the electrolyte coming into contact with the silicon-based material, improving the structural stability of the negative electrode material, and improving the cycle characteristics of the battery.
[0017] The manufacturing method of the present invention can be applied to large-scale production, and the manufactured negative electrode material can effectively improve the charge-discharge cycle stability of lithium batteries and effectively reduce the expansion rate of the negative electrode material. [Brief description of the drawings]
[0018] [Figure 1] 2 is a flowchart of a method for manufacturing a negative electrode material according to an embodiment of the present invention. [Diagram 2] 1 is a scanning electron microscope (SEM) photograph of the negative electrode material prepared in Example 1 of the present invention. [Diagram 3] 1 is an XRD chart of the negative electrode material produced in Example 1 of the present invention. [Figure 4]FIG. 2 is an initial charge / discharge curve diagram of the negative electrode material prepared in Example 1 of the present invention. [Diagram 5] FIG. 2 is a cycle characteristic curve diagram of the negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The following are preferred embodiments of the present invention, and it is understood that those skilled in the art can make some improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also within the scope of protection of the present invention.
[0020] In one embodiment of the negative electrode material, the negative electrode material has an aggregate including a carbon material and a silicon-based material, the porosity W of the negative electrode material is 2.5% or less, and the number ratio P of particles having a pore size of more than 50 nm to the number of particles in the negative electrode material is 1% or less; The porosity of the negative electrode material is determined by a measurement method for negative electrode materials, which is characterized by measuring a pore volume ΔV of the negative electrode material by a pore distribution analysis method, measuring a true density P of the negative electrode material, and then calculating the porosity of the negative electrode material by the following formula. W = ΔV / (ΔV+1 / P)
[0021] The negative electrode material according to the present embodiment has an aggregate containing an active material and a carbon material. The porosity W of the negative electrode material is 2.5% or less, and within this range, it can effectively prevent the electrolyte from directly penetrating into the inside of the negative electrode material particles through the porous structure, and effectively avoid the side reaction caused by the contact between the electrolyte and the silicon-based material; furthermore, by controlling the quantity ratio of the particles with a pore size of more than 50 nm in the negative electrode material to the negative electrode material, the electrolyte is less likely to penetrate into the aggregate, and the side reaction between the electrolyte and the silicon-based material is further avoided; the aggregate structure contributes to protecting the silicon-based material particles inside, and can effectively suppress the volume expansion of the negative electrode material, reduce the expansion rate, prevent the structure from collapsing, and improve the cycle characteristics of the battery.
[0022] When the porosity W of the negative electrode material is 2.5% or less, the porosity of the negative electrode material is low, i.e., the density of the negative electrode material is high, which contributes to improving the energy density of the composite material; on the other hand, even if the surface layer of the highly dense material is destroyed, the electrolyte is less likely to penetrate into the inside of the aggregate, which contributes to protecting the internal silicon-based material particles and reduces the probability of the electrolyte coming into contact with the silicon-based material, thereby contributing to the formation of a stable solid electrolyte membrane; furthermore, the highly dense aggregate has high fracture strength, which can eliminate the stress effect caused by expansion, improve the structural stability of the negative electrode material, effectively suppress the volume expansion of the negative electrode material, reduce the expansion rate, and improve the cycle characteristics of the battery.
[0023] In some embodiments, the porosity of the negative electrode material may be specifically, but not limited to, 2.5%, 2.4%, 2.3%, 2.2%, 2.1%, 2.0%, 1.9%, 1.6%, 1.5%, 1.2%, 0.5%, or 0.01%, and of course, may be other values within the above range. It is understood that when the negative electrode material has a low porosity, i.e., a high density, it forms a stable solid electrolyte film and contributes to reducing the contact between the electrolyte and the active material.
[0024] In some embodiments, the breaking strength of the negative electrode material particles is 400 MPa or more. Specifically, the breaking strength of the negative electrode material particles may be specifically 400 MPa, 410 MPa, 420 MPa, 450 MPa, 480 MPa, 490 MPa, 500 MPa, 550 MPa, 580 MPa, 600 MPa, etc., and of course, may be other values within the above range, but is not limited thereto. Since the negative electrode material particles have a strong rigidity, the particle structure is highly stable and can resist a certain volume expansion stress, thereby reducing the expansion and improving the cycle stability of the battery.
[0025] In some embodiments, the silicon-based material includes at least one selected from the group consisting of elemental silicon, silicon oxide materials, and silicon alloys. Examples of silicon alloys include silicon-lithium alloys and silicon-magnesium alloys. The silicon oxide material is represented by the general formula SiO x(0 <x<2)であってもよく、SiO、SiO 0.2 , SiO 0.5 , SiO 0.7 , SiO 0.9 , SiO 1.5 , SiO 1.6 or SiO 1.9 etc.
[0026] In some embodiments, the silicon-based material is a particle, and the median diameter is 1 nm to 500 nm. Specifically, it may be 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, or 500 nm, and of course, it may be other values within the above range, but is not limited thereto. Nano-order silicon-based materials have high structural stability and can suppress volume expansion. However, nano-order silicon-based materials have high surface energy and tend to aggregate during charging and discharging, and in addition, the particle diameter of the silicon-based material is too small, and the manufacturing cost is high. Therefore, preferably, the median diameter of the silicon-based material is 1 nm to 200 nm, more preferably 1 nm to 100 nm.
[0027] In some embodiments, the carbon material comprises at least one selected from the group consisting of artificial graphite, natural graphite, soft carbon, hard carbon, amorphous carbon, activated carbon, mesocarbon microbeads, carbon nanotubes, carbon nanofibers, porous carbon, and graphene. In some embodiments, the mass ratio of the silicon-based material to the carbon material is (10-70):(10-50). Specifically, it may be 10:10, 20:30, 20:50, 25:30, 30:45, 40:50, 60:50, 70:50, etc. Of course, it may be other values within the above range, and is not limited thereto. In some embodiments, the aggregate further comprises a metal oxide, which can reduce the expansion of the silicon-based material and improve the long cycle properties and fracture strength by combining the metal oxide with the silicon-based material. In some embodiments, the aggregates have the metal oxide distributed in the silicon based material and the carbon material packed between the silicon based material and the metal oxide. In some embodiments, the silicon-based material has a porous structure filled with carbon material and metal oxide. It is understood that the carbon material and metal oxide can fill the pores of the silicon-based material to improve the structural stability of the aggregate, resist a certain volume expansion stress, and reduce the expansion. In some embodiments, the carbon material has a porous structure filled with silicon-based materials and metal oxides.
[0028] In some embodiments, the metal oxide has the general formula: x O y (wherein 0.2≦y / x≦3; M includes at least one selected from the group consisting of Sn, Ge, Fe, Cu, Ti, Na, Mg, Al, Ca, and Zn). Specifically, the metal oxide may be GeO2, SnO2, ZnO, TiO2, Fe3O4, MgO, CuO, etc. The selected metal oxide has a lower volume expansion change rate during lithium absorption than the silicon-based material, so that by combining the metal oxide with the silicon-based material, the expansion of the silicon-based material can be reduced and the long cycle characteristics can be improved. In some embodiments, the metal oxide is in sheet and / or elongated form. In some embodiments, the metal oxide has an aspect ratio greater than 2. When the metal oxide is elongated, the aspect ratio is specifically the ratio of particle length to particle diameter, where the particle diameter refers to the maximum linear distance between both points on the cross-sectional periphery of the elongated conductive reinforcing agent that intersects the longitudinal direction, and when the metal oxide is sheet-shaped, the aspect ratio is specifically the ratio of the length to the width of the sheet-shaped metal oxide. Specifically, the aspect ratio of the metal oxide may be 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 12, 15, 17, 18, 22, or of course, may be other values within the above range, but is not limited thereto. As a result of repeated testing, it has been found that when the aspect ratio of the metal oxide is greater than 2, the physical bonding strength between the metal oxide and the silicon-based material is improved, thereby further mitigating the volume expansion change of the silicon-based material and improving the cycle characteristics.
[0029] In some embodiments, the mass ratio of the metal oxide to the silicon-based material is (1-20):100. Specifically, the mass ratio of the metal oxide to the silicon-based material may be 1:100, 1.5:100, 2:100, 3:100, 4.5:100, 5:100, 6:100, 7:100, 8:100, 9:100, etc. Of course, other values within the above range may also be used, and are not limited thereto. If the content of the metal oxide is too high, the initial efficiency of the material will decrease, and if the content of the metal oxide is too low, the rigidity to the aggregate structure will decrease, and the cycle stability of the particles will decrease. The negative electrode material further comprises a carbon layer coated on at least a portion of the surface of the aggregate, and preferably the carbon layer is distributed on the surface of the aggregate. In some embodiments, the carbon layer comprises amorphous carbon. In some embodiments, the thickness of the carbon layer is 1 nm to 3000 nm. It is understood that the carbon layer covering the surface of the aggregate can reduce the contact between the active material and the electrolyte, reduce the generation of a passivation film, and improve the reversible capacity of the battery. Specifically, the thickness of the carbon layer may be 1 nm, 50 nm, 180 nm, 200 nm, 350 nm, 400 nm, 550 nm, 850 nm, 950 nm, 1050 nm, 1500 nm, 2000 nm, 2500 nm or 3000 nm, and of course, may be other values within the above range, but is not limited thereto. If the carbon layer is too thick, the proportion of carbon is too high, which is disadvantageous for obtaining a composite material with a high specific capacity, and if the carbon layer is too thin, it is disadvantageous for increasing the conductivity of the negative electrode material, and the suppression performance against the volume expansion of the material is weak, which deteriorates the long cycle performance. Preferably, the thickness of the carbon layer is 50 nm to 800 nm, more preferably, the thickness of the carbon layer is 100 nm to 500 nm.
[0030] In some embodiments, the negative electrode material in which the surface of the aggregate is coated with a carbon layer has a porosity of 2.5% or less and a breaking strength of 400 MPa or more. By maintaining the porosity and breaking strength of the entire negative electrode material within the above ranges, the performance of the negative electrode material can be further improved. In some embodiments, the median diameter of the negative electrode material is 0.5 μm to 30 μm. Specifically, it may be 0.5 μm, 1 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 25 μm, 30 μm, etc., and of course, it may be other values within the above range, but is not limited thereto. It is understood that controlling the median diameter of the negative electrode material within the above range contributes to improving the cycle characteristics of the negative electrode material. In some embodiments, the specific surface area of the negative electrode material is less than 10 m 2 / g or less. 2 / g, 8m 2 / g, 7m 2 / g, 5m 2 / g, 3m 2 / g, 2m 2 / g, 1m 2 / g or 0.5m 2 / g, and of course, may be other values within the above range, but are not limited thereto. It is understood that controlling the specific surface area of the negative electrode material within the above range contributes to suppressing volume expansion and contributes to improving the cycle characteristics of the negative electrode material. In some embodiments, the breaking strength of the negative electrode material particles is 400 MPa or more, specifically, it may be 420 MPa, 440 MPa, 460 MPa, 500 MPa, 600 MPa, 700 MPa, 800 MPa, etc., and of course, it may be other values within the above range, but is not limited thereto. It is understood that controlling the breaking strength of the negative electrode material within the above range contributes to suppressing the structure of the negative electrode material from being broken, and contributes to improving the cycle characteristics of the negative electrode material. The negative electrode materials of the above embodiments can be combined in any manner as long as they are not inconsistent with each other. For example, the breaking strength and porosity of the negative electrode material particles are combined to define the combination.
[0031] In another aspect, a method for producing a negative electrode material, as shown in FIG. A step S10 of classifying and mixing a carbon material, a silicon-based material, and a solvent to obtain a first precursor; A step S20 of mixing the first precursor, a first carbon source, and an antifoaming agent and performing a densification treatment to obtain a second precursor; A step S30 of carbonizing the second precursor to obtain an aggregate, The classifying and mixing step provides a method including a vacuum impregnation process.
[0032] In the manufacturing method of this embodiment, the carbon material, the silicon-based material and the solvent are classified and mixed, and then vacuum impregnation is performed to obtain the first precursor, and the first precursor, the first carbon source and the antifoaming agent are mixed and carbonized to obtain an aggregate. In this process, the classified mixing improves the mixing uniformity of the different materials, reduces the voids caused by the deposition of the different materials, improves the deposition density, and reduces the holes caused by the deposition as much as possible. The vacuum impregnation process utilizes the action of the vacuum to further remove the gas adsorbed on the surface of the product, and further reduces the porosity. The addition of the antifoaming agent can reduce or remove the bubbles formed by the volatile matter during the carbonization process, which further contributes to the release of the volatile matter from the material. The first carbon source generally produces a large amount of volatile matter during carbonization, and if these volatile matter are not released quickly, they tend to remain inside after curing and form voids. The antifoaming agent is added, and the uniformly dispersed antifoaming agent penetrates into the foamed elastic film and is further distributed in the film, causing the foamed elastic film to crack due to the reduction in surface tension, which contributes to the smoother escape of volatile matter; and through densification treatment, some pores are further reduced, making the material more dense, reducing the porosity of the final negative electrode material, making it difficult for the electrolyte to penetrate into the aggregates, which contributes to protecting the internal silicon-based material particles, reducing the probability of the electrolyte contacting the silicon-based material, improving the structural stability of the negative electrode material, effectively suppressing the volume expansion of the negative electrode material, reducing the expansion rate, and improving the cycle characteristics of the battery.
[0033] The production method of the present invention will be specifically described below with reference to examples. Prior to step S10, the method further comprises: The method further includes carbonizing the carbon source and subjecting it to a pore-forming treatment to obtain a carbon material having a porous structure.
[0034] In some embodiments, the carbon source comprises at least one selected from the group consisting of plant-derived shells, such as coconut shells, apricot shells, rice husks, peanut shells, and hazelnut shells. In some embodiments, the carbonization temperature is 600°C to 1200°C, and may be, for example, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc. Preferably, the carbonization temperature is 600°C to 1000°C. In some embodiments, the time for the carbonization treatment may be 1 h to 10 h, such as 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 8 h, 9 h, or 10 h. In some embodiments, the temperature rise rate during the carbonization treatment is 1° C. / min to 30° C. / min, and specifically may be 1° C. / min, 5° C. / min, 10° C. / min, 15° C. / min, 20° C. / min, 25° C. / min, 30° C. / min, etc. For example, the temperature rise rate during the carbonization treatment is preferably 1° C. / min to 15° C. / min. In some embodiments, a protective gas is bubbled through during the carbonization process, and the protective gas comprises at least one selected from the group consisting of nitrogen, helium, neon, argon, and krypton.
[0035] In some embodiments, the method further comprises subjecting the carbon material to an oxidative activation treatment. Specifically, the oxidative activation treatment is carried out as follows: The carbon material is subjected to the oxidative activation treatment by being placed in a mixed gas containing at least one gas selected from the group consisting of air, carbon dioxide gas, and water vapor. In some embodiments, the temperature of the oxidation activation treatment is 400°C to 1200°C, and may be specifically 400°C, 500°C, 680°C, 700°C, 820°C, 850°C, 880°C, 900°C, 1000°C, 1100°C, or 1200°C, etc., and the time of the oxidation activation treatment is 1h to 13h, and may be specifically 1h, 3h, 5h, 7h, 9h, 10h, 12h, or 13h, etc. In some embodiments, the method further comprises, prior to step S10: The method further includes immersing a carbon source in a mixed acid solution to form pores therein, thereby obtaining a carbon material having a porous structure. In some embodiments, the mixed acid solution comprises concentrated sulfuric acid and nitric acid in a mass ratio of 1: (1-45). Specifically, the mass ratio of concentrated sulfuric acid and nitric acid may be specifically 1:1, 1:2, 1:5, 1:10, 1:20, 1:25, 1:30, 1:35, 1:40, or 1:45, etc., and of course, may be other values within the above range, but is not limited thereto. In some embodiments, the method further comprises, prior to step S10: The method further includes forming pores in the silicon-based material to obtain a silicon-based material having a porous structure. Specifically, silicon powder, silver nitrate, a corrosion aid, and deionized water may be mixed uniformly, and then hydrofluoric acid and hydrogen peroxide are added in that order to cause a corrosion reaction. The mixture is then filtered, washed, and dried to obtain a silicon-based material containing a porous structure. Here, the mass ratio of silicon powder, silver nitrate, corrosion aid, and deionized water is (10-40):(1-5):(50-200):(50-500). The corrosion aid may contain at least one selected from the group consisting of propanol, ethanol, acetic acid, hydrochloric acid, tert-butanol, and polyethylene glycol. The corrosion reaction time is 1-5 h, and specifically may be 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 5 h, etc. The hydrofluoric acid concentration is 10-30 mass%, and the hydrogen peroxide concentration is 5-45 mass%.
[0036] In step S10, the carbon material, the silicon-based material, and the solvent are classified and mixed to obtain a first precursor. The classified and mixed step includes a vacuum impregnation process. In some embodiments, the carbon material, the silicon-based material and the solvent are mixed and classified, and then dried to obtain the first precursor. Specifically, the carbon material, the silicon-based material and the solvent are mixed by classification. As a specific process, the silicon-based material and the solvent may be mixed to form a first pre-mixture, and then the carbon material and the first pre-mixture may be mixed, or the carbon material and the solvent may be mixed to form a second pre-mixture, and then the first pre-mixture and the second pre-mixture may be mixed to achieve classification mixing. It is understood that those skilled in the art can select a suitable classification mixing operation according to the specific components of the active material, the first carbon source and the solvent, according to the principle of classification mixing, so as to thoroughly mix the active material. Classification mixing promotes the contact between different active materials to be more intimate, reduces the voids caused by particle deposition, and improves the deposition density, thereby obtaining a material with low porosity. In some embodiments, a silicon-based material and a solvent are mixed to form a first premixture, and the first premixture is impregnated with a carbon material and mixed thoroughly. Specifically, the first premixture is added to a vacuum impregnation tank for impregnation, the vacuum pressure of the vacuum impregnation tank is 50 Pa or less, and the impregnation time is 0.5 h to 12 h. The vacuum immersion treatment of the premixture utilizes the effect of the vacuum to further reduce adsorbed gas, bubbles, etc. in the premixture, which contributes to obtaining a low porosity material for subsequent processing.
[0037] In some embodiments, the silicon-based material comprises one or a combination of at least two selected from the group consisting of elemental silicon, silicon alloys, and silicon oxides. Specifically, the silicon alloy may be a silicon lithium alloy, a silicon magnesium alloy, etc. The silicon oxide material is represented by the general formula SiO x (0 <x<2)であってもよく、SiO、SiO 0.2 , SiO 0.5 , SiO 0.7 , SiO 0.9 , SiO 1.5 , SiO 1.6 or SiO 1.9 etc.
[0038] In some embodiments, the silicon-based material is a particle, and the median diameter of the silicon-based material is 1 nm to 500 nm. Specifically, it may be 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, or 500 nm, and of course, it may be other values within the above range, and is not limited thereto. As a result of repeated tests, it was found that nano-order silicon-based materials have high surface energy, tend to aggregate during charging and discharging, have high particle structure, and can suppress the expansion of silicon volume. However, nano-order silicon-based materials tend to aggregate during charging and discharging because of their high surface energy. Silicon-based materials have too small particle diameters, and are expensive to manufacture. Preferably, the median diameter of the silicon-based material is 1 nm to 200 nm, more preferably 1 nm to 100 nm. In some embodiments, the carbon material has a porous structure and comprises at least one selected from the group consisting of artificial graphite, natural graphite, soft carbon, hard carbon, amorphous carbon, activated carbon, mesocarbon microbeads, carbon nanotubes, carbon nanofibers, porous carbon, and graphene.
[0039] In some embodiments, the mass ratio of the silicon-based material to the carbon material is (10-70):(10-50). Specifically, it may be 10:10, 20:30, 20:50, 25:30, 30:45, 40:50, 60:50, 70:50, etc. Of course, it may be other values within the above range, and is not limited thereto. In some embodiments, the solvent comprises an organic solvent, the organic solvent comprising at least one selected from the group consisting of methanol, ethanol, ethylene glycol, propanol, isopropanol, glycerin, n-butanol, isobutanol, and pentanol. In some embodiments, a metal oxide is further added in the step of classifying and mixing the carbon material, the silicon-based material, and the solvent. In some embodiments, the metal oxide has the general formula: x O y(wherein 0.2≦y / x≦3; M includes at least one selected from the group consisting of Sn, Ge, Fe, Cu, Ti, Na, Mg, Al, Ca, and Zn). In some embodiments, the metal oxide is in sheet and / or elongated form. In some embodiments, the aspect ratio of the metal oxide is greater than two.
[0040] In some embodiments, the mass ratio of the metal oxide to the active material is (1-20):100. Specifically, the mass ratio of the metal oxide to the active material may be 1:100, 1.5:100, 2:100, 3:100, 4.5:100, 5:100, 6:100, 7:100, 8:100, 10:100, 15:100, 20:100, etc. Of course, other values within the above range may also be used, and are not limited thereto. If the content of the metal oxide is too high, the initial efficiency of the material will decrease, and if the content of the metal oxide is too low, the rigidity to the aggregate structure will decrease, and the cycle stability of the particles will decrease. In some embodiments, the preparation of the first precursor further comprises dispersing the sieved mixture. In some embodiments, the dispersion treatment includes at least one selected from the group consisting of mechanical stirring, ultrasonic dispersion, and grinding dispersion. Preferably, grinding dispersion is adopted to disperse the silicon-based material, avoid the silicon-based material from agglomerating, and disperse the silicon-based material into relatively small nanoparticles. Preferably, the silicon-based material is sufficiently ground by a wet ball mill, which can have a dispersion time of 0.5h to 10h, to mix the components more uniformly, and the particle size of the silicon-based material particles can be 1nm to 500nm. In some embodiments, after the carbon material, the silicon-based material, and the solvent are mixed, the solvent is removed to obtain a first precursor. The form of removing the solvent includes a drying process.
[0041] In some embodiments, the temperature of the drying process is 40°C to 600°C, specifically, 40°C, 50°C, 80°C, 100°C, 120°C, 250°C, 380°C, 400°C, 500°C, 580°C, or 600°C, etc., the time of the drying process is 1h to 15h, specifically, 1h, 3h, 5h, 7h, 9h, 10h, 12h, or 15h, etc., and the drying process method may be, for example, oven drying, freeze drying, stirring evaporation to dryness, spray drying, etc., and the drying process in this embodiment can remove as much of the solvent in the precursor solution as possible. The first precursor after drying may be dispersed, and the dispersion may be abrasive dispersion, and the dispersion time is 0.5h-9h, specifically, 0.5h, 1.5h, 2.5h, 3.5h, 4.5h, 5.5h, 7.5h or 9h, etc., and the particle size after dispersion is controlled by abrasive dispersion in this embodiment. In step S20, the first precursor, the first carbon source and the antifoaming agent are mixed and densified to obtain a second precursor. It is understood that the addition of an antifoaming agent during the carbonization process can reduce or remove bubbles formed by volatile matter, further contributing to the release of volatile matter and contributing to a reduction in the porosity of the negative electrode material.
[0042] In some embodiments, the first carbon source comprises at least one selected from the group consisting of sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, and asphalt. In some embodiments, the antifoaming agent comprises at least one selected from the group consisting of cetylbenzenesulfonic acid, polyether modified silicone oil, monoamides, bisamides, trialkylmelamines, cyanuric acid chloride melamine, aliphatic amines, lauric acid, palmitic acid, fatty acid glycerides, polydimethylsiloxanes, polyacrylic acid, ethylene oxide, and propylene oxide. In some embodiments, the mass ratio of the first precursor to the first carbon source is (10-80):(100), and specifically may be 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 50:100, 60:100, 80:100, etc. If the mass ratio of the first precursor to the first carbon source is too high, the capacity of the material is reduced, and in some embodiments, if the mass proportion of non-graphitizable carbon is too high, the initial efficiency of the material is also reduced. In some embodiments, the mass ratio of the first precursor to the antifoaming agent is (10 to 80):(0.4 to 14), and specifically may be 10:0.4, 15:1, 20:1.5, 25:2, 30:5, 35:7, 50:8, 60:10, or 80:14, etc.
[0043] In some embodiments, the densification process comprises at least one selected from the group consisting of a fusion process, a kneading-extrusion process, an embossing process, and a dipping process. In some embodiments, the fusion process is mechanofusion. The fusion process of the first precursor improves the fracture strength of the negative electrode material particles, and the heat treatment strengthens the stability of the particle structure, improves the connection stability between the active material and the first carbon source, and reduces the porosity. Of course, in other embodiments, the densification process may be performed by a method other than the above, such as pressing or immersion, as long as the porosity of the aggregate can be 2.5% or less and the fracture strength can be 400 MPa or more. In some embodiments, the porosity of the final negative electrode material is 2.5% or less, and the crushing strength of the negative electrode material particles is 400 MPa or more. In this case, the porosity and crushing strength of the aggregates can be controlled according to the final carbon layer conditions to achieve the target porosity and crushing strength of the final negative electrode material. In some embodiments, during fusion, the rotation speed of the fusion device is 30 r / min to 100 r / min, specifically, 30 r / min, 40 r / min, 50 r / min, 60 r / min, 70 r / min, 80 r / min, 100 r / min, etc., and the fusion time is at least 0.5 h, specifically, 0.5 h, 0.8 h, 0.9 h, 1.0 h, 1.5 h, 2 h, etc., but is not limited thereto.
[0044] In step S30, the second precursor is carbonized to obtain an aggregate. In some embodiments, the carbonization temperature is 600°C to 1200°C, and may be, for example, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc. Preferably, the carbonization temperature is 600°C to 1000°C. In some embodiments, the time for the carbonization treatment may be 1 h to 10 h, such as 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h. In some embodiments, the temperature rise rate during the carbonization treatment is 1° C. / min to 30° C. / min, and specifically may be 1° C. / min, 5° C. / min, 10° C. / min, 15° C. / min, 20° C. / min, 25° C. / min, 30° C. / min, etc. For example, the temperature rise rate during the carbonization treatment is preferably 1° C. / min to 15° C. / min. In some embodiments, a protective gas is bubbled through during the carbonization process, and the protective gas comprises at least one selected from the group consisting of nitrogen, helium, neon, argon, and krypton.
[0045] The method further includes a step S40 of carbon coating the aggregates. In some embodiments, in step S40, the aggregates are mixed with a second carbon source and subjected to a carbon coating process. In some embodiments, the second carbon source comprises at least one selected from the group consisting of sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, and asphalt. In some embodiments, mixing techniques may include magnetic stirring, mechanical stirring, ultrasonic dispersion, abrasive dispersion, and the like. In some embodiments, the mass ratio of the aggregate to the second carbon source is (20-100):(10-80). The mass ratio of the aggregate to the second carbon source may be, but is not limited to, 20:10, 30:15, 50:60, 80:30, 90:20, 100:10, etc., and may of course be other values within the above range. In some embodiments, the carbon coating process may be, for example, vacuum sintering, hot press sintering, or pressureless sintering. The temperature of the carbon coating process may be 600°C to 1200°C, such as 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc. Preferably, the temperature of the carbon coating process is 600°C to 1000°C.
[0046] In some embodiments, the time for the carbon coating treatment may be between 1 h and 10 h, such as 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h. In some embodiments, the carbon coating process is carried out in a protective atmosphere, the protective atmosphere gas comprising at least one selected from the group consisting of nitrogen, helium, neon, argon and krypton. The carbon coating treatment in step S40 may not be necessary, and the aggregate obtained in the carbonization treatment in step S30 may be used as the negative electrode material as it is, and is not limited thereto. In some embodiments, after the carbon coating treatment, at least one selected from the group consisting of pulverization, sieving, and demagnetization is further performed, and preferably, after the carbon coating treatment, pulverization, sieving, and demagnetization are further performed in this order. In some embodiments, the grinding method is any one selected from a mechanical grinder, an airflow grinder, and a cryogenic grinder. In some embodiments, the sieving method is any one selected from a fixed sieve, a drum screen, a resonating sieve, a roll screen, a vibrating sieve, and a chain screen, and the mesh number of the sieving is 500 mesh or more. Specifically, the mesh number of the sieving may be 500 mesh, 600 mesh, 700 mesh, 800 mesh, etc., and controlling the particle size of the negative electrode material within the above range contributes to improving the cycle characteristics of the negative electrode material.
[0047] In some embodiments, the demagnetizing device is any one selected from a permanent magnet drum type magnetic separator, an electromagnetic separator, and a pulsating high gradient magnetic separator, and the demagnetizing is to finally control the magnetic material content of the negative electrode material so as to avoid the discharging effect of the magnetic material on the lithium ion battery and the impact on the safety of the battery during use. The median size in this specification refers to the average particle size, and its physical meaning is the particle size when the cumulative particle size distribution percentage of the particles reaches 50%, which is measured by a Malvern particle sizer. The Malvern particle sizer uses the phenomenon of light scattering by particles to comprehensively convert the particle size distribution of the measured particles based on the distribution of scattered light energy.
[0048] The present invention provides a lithium ion battery having the above-mentioned negative electrode material. The present invention will be further described below with reference to several examples. However, the examples of the present invention are not limited to the following specific examples. The present invention can be modified appropriately without departing from the spirit of the present invention.
[0049] Example 1 The method for producing the negative electrode material according to this embodiment is as follows: A step (1) of carbonizing coconut shells at 600°C for 6 hours under air-blocking conditions, and then oxidizing and activating the coconut shells with air, carbon dioxide, water vapor or a mixture thereof at 900°C to obtain a porous carbon material; (2) mixing nanosilicon having a particle size of 200 nm with butanol solvent to form nanosilicon slurry, adding the dispersed nanosilicon slurry to a vacuum impregnation tank, then adding porous carbon, setting the vacuum pressure to 150 Pa, soaking for 5 h, and drying to obtain a first precursor; (3) mixing the obtained first precursor and a phenolic resin in a mass ratio of 100:35, adding 3 mass% of lauric acid, mixing uniformly, placing in a kneading device, kneading at a rotation speed of 40 r / min for a processing time of 30 min, and obtaining a second precursor; The mixed material is placed in a high-temperature box furnace, nitrogen is introduced, and the material is carbonized at 800 ° C for 3 hours. Then, the material is pulverized and passed through a 500 mesh sieve to obtain an aggregate (4); and (5) mixing the aggregates and sucrose in a mass ratio of 20:10, followed by carbon coating treatment under a nitrogen atmosphere at a temperature of 750° C. for a time of 8 hours to obtain a negative electrode material.
[0050] The negative electrode material produced in this example has an aggregate containing nanosilicon powder and porous carbon, at least a portion of which is filled in the porous structure of the porous carbon, and a carbon layer coated on the surface of the aggregate. The median diameter of the negative electrode material is 14 μm, and the specific surface area is 2.2 m. 2 / g, and the average thickness of the carbon layer is 460 nm. The porosity W of the negative electrode material is 1.3%, and the percentage P of particles having a pore size of more than 50 nm relative to the negative electrode material is 0.15%. The breaking strength of the negative electrode material particles is 860 MPa.
[0051] Example 2 The method for producing the negative electrode material according to this embodiment is as follows: (1) mixing nanosilicon having a particle size of 200 nm with a propanol solvent to form a nanosilicon slurry, adding the dispersed nanosilicon slurry to a vacuum impregnation tank, then adding artificial graphite, setting the vacuum pressure to 10 Pa, soaking for 9 hours, and drying to obtain a first precursor; (2) mixing the first precursor and fructose in a mass ratio of 100:55, adding 5 mass% of polyether-modified silicone oil, placing the mixture in a fusion device, setting the rotation speed to 40 r / min, fusing the mixture for 60 min, and obtaining a second precursor; (3) placing the mixed material in a high-temperature box furnace, introducing nitrogen gas, carbonizing the material at 950°C, and keeping the material at this temperature for 6 hours; then pulverizing the material and passing the material through a 500 mesh sieve to obtain the aggregates; and (4) mixing the aggregates and glucose in a mass ratio of 30:10, and then subjecting the mixture to a carbon coating treatment under a nitrogen atmosphere, the temperature of the carbon coating treatment being 800° C., the time of the carbon coating treatment being 8 hours, thereby obtaining a negative electrode material.
[0052] The negative electrode material produced in this example has an aggregate containing nanosilicon powder and artificial graphite, and a carbon layer coated on the surface of the aggregate. The median diameter of the negative electrode material is 16 μm and the specific surface area is 2.5 m. 2 / g, and the average thickness of the carbon layer is 420 nm. The porosity W of the negative electrode material is 1.1%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 0.2%. The breaking strength of the negative electrode material particles is 770 MPa.
[0053] Example 3 The method for producing the negative electrode material according to this embodiment is as follows: A step (1) of placing graphite in a mixture of concentrated sulfuric acid and nitric acid (mass ratio 1:1) to perform a hollowing treatment to obtain porous graphite; (2) mixing nanosilicon having a particle size of 80 nm with an ethanol solvent to form a nanosilicon slurry, adding the dispersed nanosilicon slurry to a vacuum impregnation tank, then adding porous graphite, setting the vacuum pressure to 15 Pa, soaking for 9 hours, and drying to obtain a first precursor; (3) mixing the first precursor and sucrose in a mass ratio of 100:55, adding 2 mass% palmitic acid, placing the mixture in a kneading device, kneading the mixture at a rotation speed of 80 r / min for a processing time of 90 min, and obtaining a second precursor; (4) placing the mixed material in a high-temperature box furnace, introducing nitrogen, carbonizing the material at 850°C, and keeping the material at this temperature for 6 hours, and then pulverizing the material and passing the material through a 500 mesh sieve to obtain the aggregates; and (5) mixing the aggregate and acrylic resin in a mass ratio of 40:10, and then subjecting the mixture to a carbon coating treatment under a nitrogen atmosphere, the carbon coating treatment temperature being 650° C., the carbon coating treatment time being 6 hours, thereby obtaining a negative electrode material.
[0054] The negative electrode material produced in this example has an aggregate containing nanosilicon powder and porous graphite, and a carbon layer coated on the surface of the aggregate. The negative electrode material has a median diameter of 11 μm and a specific surface area of 3.2 m. 2 / g, and the average thickness of the carbon layer is 330 nm. The porosity W of the negative electrode material is 2.2%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 0.55%. The breaking strength of the negative electrode material particles is 512 MPa.
[0055] Example 4 The method for producing the negative electrode material according to this embodiment is as follows: (1) mixing nanosilicon having a particle size of 50 nm with a solvent pentanol to form a nanosilicon slurry, adding the dispersed nanosilicon slurry to a vacuum impregnation tank, then adding artificial graphite, setting the vacuum pressure to 37 Pa, soaking for 8 hours, and drying to obtain a first precursor; (2) mixing the first precursor and the resin in a mass ratio of 100:45, adding 5 mass% of polydimethylsiloxane, and mixing uniformly to obtain a second precursor; (3) placing the mixed material in a high-temperature box furnace, introducing nitrogen gas, carbonizing the material at 1050°C, and keeping the material warm for 2 hours, and then pulverizing the material and passing the material through a 500 mesh sieve to obtain the aggregates; and (4) mixing the aggregate and asphalt in a mass ratio of 50:12, and then subjecting the mixture to a carbon coating treatment under a nitrogen atmosphere, the temperature of the carbon coating treatment being 650° C., the time of the carbon coating treatment being 6 hours, thereby obtaining a negative electrode material.
[0056] The negative electrode material produced in this example has an aggregate containing nanosilicon powder and artificial graphite, and a carbon layer coated on the surface of the aggregate. The median diameter of the negative electrode material is 12.2 μm and the specific surface area is 2.9 m. 2 / g, and the average thickness of the carbon layer is 680 nm. The porosity W of the negative electrode material is 1.8%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 0.3%. The breaking strength of the negative electrode material particles is 640 MPa.
[0057] Example 5 The method for producing the negative electrode material according to this embodiment is as follows: Carbon black material was measured using the BET method to determine if its specific surface area was 50 m 2 / g or less and a porosity of 30% or more; (2) mixing nanosilicon having a particle size of 100 nm with a cyclohexane solvent to form a nanosilicon slurry, adding the nanosilicon slurry to a vacuum impregnation tank, then adding porous carbon, setting the vacuum pressure to 500 Pa, soaking for 5 h, and drying to obtain a first precursor; (3) mixing the first precursor and sucrose in a mass ratio of 90:35, adding 5% by mass of ethylene oxide, placing the mixture in a fusion device, setting the blade width to 1.1 cm, and fusing the mixture for 150 minutes to obtain a second precursor; (4) placing the mixed material in a high-temperature box furnace, introducing nitrogen gas, carbonizing the material at 1050°C, and keeping the material at this temperature for 2 hours; then pulverizing the material and passing the material through a 500 mesh sieve to obtain the aggregates; and (5) mixing the aggregate and asphalt in a mass ratio of 50:12, and then subjecting the mixture to a carbon coating treatment under a nitrogen atmosphere, the temperature of the carbon coating treatment being 650° C., the time of the carbon coating treatment being 6 hours, thereby obtaining a negative electrode material.
[0058] The negative electrode material produced in this example has an aggregate containing nanosilicon powder and porous carbon, and a carbon layer coated on the surface of the aggregate. The negative electrode material has a median diameter of 8.2 μm and a specific surface area of 2.7 m. 2 / g, and the average thickness of the carbon layer is 580 nm. The porosity W of the negative electrode material is 0.8%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 0.05%. The breaking strength of the negative electrode material particles is 923 MPa.
[0059] Example 6 Example 6 is substantially the same as Example 1, except that a nanosilicon slurry formed by mixing nanosilicon having a particle size of 600 nm with a toluene solvent is used. The negative electrode material produced in this example has an aggregate containing nanosilicon powder and porous carbon, and a carbon layer coated on the surface of the aggregate. The negative electrode material has a median diameter of 12 μm and a specific surface area of 1.9 m. 2 / g, and the average thickness of the carbon layer is 423 nm. The porosity W of the negative electrode material is 2.3%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 0.9%. The breaking strength of the negative electrode material particles is 411 MPa.
[0060] Example 7 Example 7 is substantially the same as Example 1, except that a silicon monoxide slurry formed by mixing silicon monoxide particles having a particle size of 50 nm with a butanol solvent is used. The negative electrode material produced in this example has an aggregate containing silicon monoxide and porous carbon, at least a portion of which is filled in the porous structure of the porous carbon, and a carbon layer covering the surface of the aggregate. The negative electrode material has a median diameter of 13 μm and a specific surface area of 1.85 m. 2 / g, and the average thickness of the carbon layer is 410 nm. The porosity W of the negative electrode material is 1.6%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 0.12%. The breaking strength of the negative electrode material particles is 455 MPa.
[0061] Example 8 Example 8 is substantially the same as Example 1, except that a silicon-lithium alloy slurry formed by mixing a silicon-lithium alloy having a particle size of 50 nm with a cyclohexane solvent is used. The negative electrode material produced in this example has an aggregate containing a silicon-lithium alloy and porous carbon, at least a portion of which is filled in the porous structure of the porous carbon, and a carbon layer covering the surface of the aggregate. The negative electrode material has a median diameter of 15 μm and a specific surface area of 1.94 m. 2 / g, and the average thickness of the carbon layer is 240 nm. The porosity W of the negative electrode material is 1.9%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 0.5%. The breaking strength of the negative electrode material particles is 680 MPa.
[0062] Example 9 In Example 9, the process was almost the same as in Example 1, except that in step (4), the carbonization treatment was carried out at 500° C. for 3 hours, followed by pulverization and passing through a 500 mesh sieve to obtain a negative electrode material. The negative electrode material produced in this example has an aggregate containing nanosilicon powder and porous carbon, at least a portion of which is filled into the porous structure of the porous carbon, and a carbon layer covering the surface of the aggregate. The negative electrode material has a median diameter of 13 μm and a specific surface area of 2.9 m. 2 / g, and the average thickness of the carbon layer is 450 nm. The porosity W of the negative electrode material is 1.4%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 0.16%. The breaking strength of the negative electrode material particles is 580 MPa.
[0063] Example 10 In Example 10, in step (2), nanosilicon having a particle size of 200 nm and zinc oxide ZnO are mixed in n-butanol solvent to form nanosilicon slurry, the dispersed nanosilicon slurry is added to a vacuum impregnation tank, and then porous carbon is added, the vacuum pressure is set to 150 Pa, the mixture is immersed for 5 hours, and then dried to obtain a first precursor, except that the process is almost the same as that of Example 1. The negative electrode material produced in this example has an aggregate containing nanosilicon powder and porous carbon, at least a portion of which is filled in the porous structure of the porous carbon, and a carbon layer covering the surface of the aggregate. The negative electrode material has a median diameter of 12 μm and a specific surface area of 2.0 m 2 / g, and the average thickness of the carbon layer is 490 nm. The porosity W of the negative electrode material is 1.6%, and the quantity ratio P of the particles of the negative electrode material having a pore size of more than 50 nm is 0.19%. The breaking strength of the negative electrode material particles is 590 MPa.
[0064] Example 11 Example 11 was conducted in substantially the same manner as Example 1, except that the carbon coating treatment step in step (5) was not carried out. The negative electrode material produced in this example has aggregates containing nanosilicon powder and porous carbon, at least a portion of which is filled in the porous structure of the porous carbon. The negative electrode material has a median diameter of 10 μm and a specific surface area of 2.8 m 2 / g. The porosity W of the negative electrode material is 1.8%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 0.23%. The breaking strength of the negative electrode material particles is 580 MPa.
[0065] Comparative Example 1 In step (3), a negative electrode material is produced in substantially the same manner as in Example 1, except that the fusion treatment is not carried out. The negative electrode material produced in this example has an aggregate containing nanosilicon powder and porous carbon, and a carbon layer coated on the surface of the aggregate. The negative electrode material has a median diameter of 18 μm and a specific surface area of 2.5 m. 2 / g, and the average thickness of the carbon layer is 465 nm. The porosity W of the negative electrode material is 10.2%, and the quantity ratio P of particles having a pore size exceeding 50 nm to the negative electrode material is 1.7%. The breaking strength of the negative electrode material particles is 105 MPa.
[0066] Comparative Example 2 A negative electrode material is produced in substantially the same manner as in Example 1, except that in step (3), no antifoaming agent is added.
[0067] Comparative Example 3 A negative electrode material is produced in substantially the same manner as in Example 1, except that in step (2), no classification and mixing is carried out. Specifically, in step (2), nanosilicon having a particle size of 200 nm, butanol solvent and porous carbon are added into a vacuum impregnation tank, the vacuum pressure is set to 150 Pa, and the mixture is soaked for 5 hours and then dried to obtain a first precursor.
[0068] Comparative Example 4 In step (2), a negative electrode material is produced in substantially the same manner as in Example 1, except that the vacuum impregnation treatment is not carried out. Specifically, in step (2), the dispersed nanosilicon slurry is added into a vacuum impregnation tank, then the porous carbon artificial graphite is added, soaked for 9 hours, and dried to obtain a first precursor.
[0069] Measurement method (1) Measurement of the porosity of the negative electrode material The pore volume ΔV of the negative electrode material is measured using pore distribution analysis, the true density P of the negative electrode material is measured, and the porosity of the negative electrode material is calculated as W = ΔV / (ΔV+1 / P). (2) Measurement of the quantity ratio P of particles with a pore size exceeding 50 nm in the negative electrode material The negative electrode material is measured in cross section, 100 particles are randomly counted, and the number N1 of particles having a porous structure with a pore diameter of more than 50 nm is calculated, and the number proportion P=N1 / 100≦1%. (3) Measurement of the breaking strength of negative electrode material particles The negative electrode material is extruded, and the breaking strength of each of 50 or more negative electrode material particles is measured, and the average value is taken as the breaking strength of the particle. (4) Method for measuring the median diameter of negative electrode material The median diameter, which is the average particle size of the negative electrode material, is measured using a Malvern laser diffraction particle size distribution analyzer. (5) Measurement method for the specific surface area of negative electrode material The specific surface area of the negative electrode material was measured using a Micromeritics TriStar 3020 automatic specific surface area / pore distribution measurement device. Specifically, a certain mass of the powder of the negative electrode material was weighed, heated in a vacuum to perform a complete degassing process, and any adsorbed gas on the surface was removed. The specific surface area of the particles was then calculated from the amount of adsorbed nitrogen using a nitrogen gas adsorption method. (6) Measurement method for the carbon layer thickness of the negative electrode material The material is subjected to cross-section processing using a focused ion beam scanning electron microscope (FIB-SEM) device, and the average thickness of the carbon layer is measured in the scanning electron microscope image. (7) Measurement of electrochemical performance The electrochemical cycle performance is measured by the following method. The silicon carbon composite negative electrode material, conductive agent and adhesive are dissolved and mixed in a solvent in a mass ratio of 94:1:5 so that the solid content is 50%, and then coated on a copper foil current collector and vacuum dried to produce a negative electrode sheet. Then, the ternary positive electrode sheet manufactured by conventional mature technology, 1 mol / L LiPF6 / ethylene carbonate + dimethyl carbonate + methyl ethyl carbonate (v / v = 1:1:1) electrolyte, Celgard2400 separator film and case are assembled into a button-type lithium ion battery by conventional manufacturing technology. The initial thickness H0 of the electrode piece of the lithium ion battery is measured with a micrometer. The charge and discharge test of the lithium ion battery is performed with a LAND battery measurement system manufactured by WuhanLANDelectronics Co., Ltd., at room temperature conditions, constant current charging and discharging at 0.2C, and the charge and discharge voltage is 2.75 to 4.2V. The initial reversible capacity, initial charge capacity and initial discharge capacity are obtained. Initial coulombic efficiency = Initial discharge capacity / Initial charge capacity After 50 cycles, the thickness H1 of the lithium-ion battery pole piece was measured with a micrometer, and the expansion rate after 50 cycles was calculated as (H1-H0) / H0×100%. After 100 cycles, the discharge capacity was recorded as the remaining capacity of the lithium-ion battery, and the capacity retention rate = remaining capacity / initial capacity * 100%.
[0070] The above performance measurement results are shown in the table below. Table 1 Performance comparison results [Table 1]
[0071] 4 is a diagram showing the initial charge-discharge curve of the negative electrode material prepared in Example 1 of the present invention. As shown in Fig. 4, the negative electrode material prepared in Example 1 has a high initial charge-discharge capacity and a high initial efficiency.
[0072] Fig. 5 is a cycle characteristic curve diagram of the negative electrode material prepared in Example 1 of the present invention. As shown in Fig. 5, the negative electrode material has excellent cycle characteristics, with a 100 cycle capacity retention rate of 93.5%, because the aggregates have low porosity, and the electrolyte is difficult to penetrate into the aggregates, and the aggregate structure contributes to protecting the active material particles inside, effectively suppressing the volume expansion of the negative electrode material, reducing the expansion rate, and improving the cycle characteristics of the battery.
[0073] As shown in Table 1, the negative electrode materials produced in Examples 1 to 11 have an aggregate containing an active material and a carbon material, and a carbon layer present on the surface of the aggregate. The porosity W of the negative electrode material is 2.5% or less, and by being in this range, it is possible to effectively suppress the electrolyte from directly penetrating into the inside of the negative electrode material particles through the porous structure, and effectively avoid side reactions caused by contact between the electrolyte and the silicon-based material; further, by controlling the quantitative ratio of particles with a pore size of more than 50 nm in the negative electrode material to the negative electrode material to less than 1%, the side reactions between the electrolyte and the silicon-based material are further avoided, and the electrolyte is also less likely to penetrate into the inside of the aggregate, and the aggregate structure contributes to protecting the silicon-based material particles inside, effectively suppressing the volume expansion of the negative electrode material, reducing the expansion rate, and improving the cycle characteristics of the battery.
[0074] Among them, the negative electrode material of Example 6 has a too large particle size of nanosilicon during the preparation, and the particles are easily powdered and crushed during cycling, which makes the material structure unstable and reduces the cycling performance.
[0075] In the preparation of the negative electrode material of Example 7, the particle size of the silicon-based material is too small, and the silicon-based material is prone to agglomeration during charging and discharging, which is disadvantageous to the cycle stability of the material.
[0076] In the manufacture of the negative electrode material of Example 8, a silicon-lithium alloy is used as the silicon-based material, which improves the structural strength of the silicon material, maintains a high cycle capacity retention rate, and reduces the battery expansion rate.
[0077] In the preparation of the negative electrode material of Example 9, the carbon coating temperature was too low, and the carbon source carbon coating on the surface of the aggregates was incomplete, resulting in a decrease in the conductivity of the negative electrode material and a decrease in the initial coulombic efficiency of the negative electrode material.
[0078] In the production of the negative electrode material of Example 10, a metal oxide is further added during the process of mixing the silicon-based material and the carbon material in the solvent, which improves the rigidity of the aggregate structure, improves the cycle stability of the particles, and reduces the expansion rate of the pole pieces after cycling.
[0079] In the production of the negative electrode material of Comparative Example 1, no antifoaming agent is added to the raw materials in step (3), which is disadvantageous in preventing further smooth removal of volatile matter in the first carbon source, increases the porosity of the negative electrode material, makes it easier for the electrolyte to penetrate into the aggregates, increases the probability of contact between the electrolyte and the silicon-based material, increases the volume expansion rate of the negative electrode material, and deteriorates the cycle characteristics of the battery.
[0080] In the production of the negative electrode material of Comparative Example 2, the precursor is not fused in step (3), so the overall structure tends to fall apart, the connection stability between the silicon-based material and the carbon material is low, and the number of voids between the silicon-based material and the carbon material increases, which reduces the structural strength of the aggregate, significantly reduces the fracture strength, and makes it difficult to withstand stress changes due to the active material expansion effect, resulting in an increased expansion rate.
[0081] In the production of the negative electrode materials of Comparative Examples 3 and 4, no classification / mixing or vacuum impregnation treatment is performed in step (1), so the porosity of the negative electrode material increases and the expansion rate of the electrode piece increases.
[0082] As described above, the present invention has been disclosed with reference to the preferred embodiments, but these are not intended to limit the scope of the claims. Those skilled in the art may make various possible modifications and variations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be limited only by the scope of the claims.
Claims
1. A negative electrode material having an aggregate including a carbon material and a silicon-based material, The negative electrode material has a porosity W of 2.5% or less, and a quantitative ratio P of negative electrode material particles having pores with a pore diameter of more than 50 nm therein to the negative electrode material. 1 is 1% or less, The ratio P of the number of negative electrode material particles having pores with a diameter of more than 50 nm in the negative electrode material to the number of negative electrode material particles 1 Measurement of the number N of negative electrode material particles having pores with a diameter of more than 50 nm inside: A cross section of the negative electrode material is measured, and 100 particles are randomly counted. 1 Calculate the quantity ratio P 1 = N 1 / 100≦1%, The porosity W of the negative electrode material is measured by measuring the pore volume ΔV of the negative electrode material using a pore distribution analysis method, and the true density P 2 and then calculating the porosity W of the negative electrode material by the following formula. W=ΔV / (ΔV+1 / P) 2 )
2. 2. The negative electrode material according to claim 1, wherein the aggregate comprises a carbon material having a porous structure and a silicon-based material filled in the porous structure of the carbon material.
3. 2. The negative electrode material according to claim 1, wherein the aggregate comprises a silicon-based material having a porous structure and a carbon material filled in the porous structure of the silicon-based material.
4. 2. The negative electrode material according to claim 1, wherein the particle breaking strength of the negative electrode material is 400 MPa or more.
5. The negative electrode material of claim 1 , wherein the aggregates further comprise a metal oxide.
6. 6. The negative electrode material according to claim 5, wherein the metal oxide is distributed between the carbon material and the silicon-based material.
7. 2. The negative electrode material according to claim 1, wherein the negative electrode material has a median diameter of 0.5 μm to 30 μm.
8. The negative electrode material has a specific surface area of 10 m 2 2. The negative electrode material according to claim 1, wherein the molecular weight is 1 / g or less.
9. A method for producing the negative electrode material according to any one of claims 1 to 8, comprising the steps of: A step of classifying and mixing a carbon material, a silicon-based material, and a solvent to obtain a first precursor; mixing the first precursor, a first carbon source, and a defoaming agent and subjecting the mixture to a densification treatment to obtain a second precursor; and carbonizing the second precursor to obtain an aggregate. The manufacturing method according to the present invention, wherein the classifying and mixing step includes a vacuum impregnation treatment.
10. A lithium ion battery comprising the negative electrode material according to claim 1 or 2.
Citation Information
Patent Citations
Silicon oxide / carbon composite negative electrode material, its preparation method and lithium ion battery
JP2021536102A
Negative electrode active material for lithium secondary battery, method for producing the same, and lithium secondary battery including the same
JP2022510984A
Negative active material, lithium secondary battery including the material, and method of manufacturing the material
US20180097229A1
Composite particle for negative electrode of lithium ion secondary battery
WO2020138313A1